The Effect of Microcrystalline Cellulose on the Physical, Thermal, and Mechanical Properties of Composites Based on Cantala Fiber and Recycled High-Density Polyethylene - Wijang Wisnu Raharjo; Rudi Salam; Dody Ariawan (Journal of Natural Fibers, 2023)
This research is conducted to improve the performance of plant fiber-based composites by inserting microcrystalline cellulose (MCC). MCC was incorporated into a mixture of recycled high-density polyethylene (rHDPE) and cantala fiber at a ratio of 1, 2, 3, and 4% wt. The composites rHDPE/cantala fiber/MCC were fabricated via a twin screw extruder followed by a hot press. The composite’s mechanical, physical, and thermal properties were tested to investigate the effect of adding MCC. It was observed that the enhancement of MCC led to a significant improvement in the mechanical performance of the composite. Adding 4%wt MCC resulted in a significant improvement in mechanical properties of 50.7%, 31%, and 37.7%, respectively, in tensile strength, bending strength, and impact strength compared to rHDPE/cantala composite without MCC. Adding MCC up to 4% wt slightly increased the composite density from 0.88gr/cm3 to 0.90 gr/cm3. The enhancement of MCC did not significantly change the diffraction peak position of the composite. However, composite crystallinity increased by 6.7%. In addition, the augment of MCC increased the thermal stability of the composite, as indicated by the delay in composite degradation.